2008
DOI: 10.2989/qm.2008.31.2.4.476
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive Set Theoretic Methods Applied to Strictly Singular and Strictly Cosingular Operators

Abstract: Abstract. The class of strictly singular operators originating from the dual of a separable Banach space is written as an increasing union of ω1 subclasses which are defined using the Schreier sets. A question of J. Diestel, of whether a similar result can be stated for strictly cosingular operators, is studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Since X has the Bessaga–Pełczyński property, the operator TJX is not strictly singular and hence T is also not strictly singular. It follows from [, Theorem 3.1] that T is not strictly cosingular. Hence, X has the Pełczyński property.…”
Section: Quantitative Pełczyński Propertymentioning
confidence: 99%
See 1 more Smart Citation
“…Since X has the Bessaga–Pełczyński property, the operator TJX is not strictly singular and hence T is also not strictly singular. It follows from [, Theorem 3.1] that T is not strictly cosingular. Hence, X has the Pełczyński property.…”
Section: Quantitative Pełczyński Propertymentioning
confidence: 99%
“…Remark The added assumption that X is separable is inspired by [, Theorem 3.1]. We do not know whether there are other appropriate conditions or even the condition that X is separable can be removed.…”
Section: Quantitative Pełczyński Propertymentioning
confidence: 99%
“…Denote the subclass of S ξ -strictly singular operators by S ξ -S. It is clear that S 0 -S coincides with the class of compact operators. These classes where defined in [3] and have been extensively studied [2,11,14,48]. In particular, while it is shown that (S ξ -S) ξ<ω 1 separably refines S. In general, S ξ -S need not satisfy the additive property of being an operator ideal [45].…”
Section: Weakly Compact Operators and Subclasses An Operatormentioning
confidence: 99%
“…Presently, the two most famous examples are the Szlenk and Bourgain indexes [12,19] (see [17] for a excellent exposition of both). More recently, the Schreier families (S ξ ) ξ<ω 1 (introduced in [1]) have been used to index subclasses of classes of separable Banach spaces and classes of operators between separable Banach spaces [2,3].…”
Section: Introductionmentioning
confidence: 99%